Beyond justice : death and the retribution principle in the Book of Job - Churnai, Varunaj (Carlisle, Cumbria, UK, Langham Monographs, 2018)
In recent decades, scholars have tended to interpret what Job says about death in one of two ways. The interpret it either as part of the broader reading of death in the Old Testament or by imposing Ancient Near Eastern mythological concepts upon the text disregarding its nature as part of the Old Testament's wisdom tradition. Varunaj Churnai attempts to redress the latter interpretation and treats the book of Job, and its development and understanding of death, contextually. Churnai specifically looks at how Job presents the two faces of God: God's wrathful face and God's gracious face. Beyond Justice demonstrates that the retribution principle allows humans to know the hidden God as it illuminates the relationship between individual and Creator. Through Job's experiences and heartfelt outpouring of his soul before both God's wrathful face and God's gracious face we can know God more fully. Churnai shows how these faces of God are reconciled in the two divine speeches of YHWH, which invite both Job and the reader to move beyond retribution theology to trust in the graciousness of God.
Keywords: Bible.-- Job; Bible.-- Job.-- Criticism, interpretation, etc; Death.-- Biblical teaching; Retribution.-- Religious aspects, Christianity